Etika a správce daně - Gapko, Petr (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá aktuálním tématem „Etika a správce daně ‘‘. Jsou zde zachyceny dva různé etické pohledy a to samotných správců spotřební daně a plátců spotřební daně. Cílovou skupinou pro vypracování návrhu etického chování správců daně jsou příslušníci Celní správy ČR – správci spotřební daně. V obecné části jsou vymezeny především základní pojmy a cíl bakalářské práce. Podrobněji je popisována komunikace daňových subjektů a správců daně, vzdělávání a právní podvědomí správců daně, jejich korupce a trestná činnost a s tím spojená problematika. Praktická část se zabývá metodou dotazníkovým šetřením, přípravou dotazníků, vytipováním vhodných respondentů a jejich oslovení. Závěrečná část bakalářské práce obsahuje vyhodnocení jak se podařilo realizovat hlavní cíl a dílčí cíle a jaké problémy, potíže se vyskytly.

This bachelorۥs thesis explores a very topical subject of ۥۥThe Ethics and Tax Administratorsۥۥ. There are two different moral attitudes expressed, the first by the tax administrators themselves and the second by purchase tax payers. The target group for developing a project of tax administratorsۥ ethical behaviour are members of customs service, that is to say, purchase tax administrators. In the general part, the basic terms together with the aim of the thesis are defined. Communations among tax subjects and tax administrators is described in detail as well as eduration, tax administratorsۥ legal awareness, their corruption, criminality and other related issues. The practical part deals with a method of questionnaires, their preparation, prediction of suitable informats and their addressing. The concluding part of the thesis contains an evaluation of how well the main and component aims were achieved, and what difficulties and problems have occurred.
The ethics and tax administrators
Keywords: ethics; Criminality; Corruption; customs service; consumer tax; etika; trestná činnost; Korupce; celní správa; spotřební daň